The moral economy and Islamic economics: is there any place for universal man? - Mohd Yusop, Mohd Mahyudi (2019)
According to Gotz (2015), the origin of the phrase ‘moral economy’ is attributed to E. P. Thompson (1971). Since then, its historical evolution sees its usage to enter into a wide array of fields of study; including history, anthropology, political science and economics. Notably, starting primarily with welfare state policy instruments, the importance of the concept has been given more attention by economists, despite the fact that there is no consensus concerning how best to define and use that neologism. At least in economics, the moral deficiency and greed factors that led to the recent global financial crises could be viewed as possible reasons for the rise in interest about the idea of moral economy. Interestingly, Islamic economists claim that Islamic economics is also one big project of Islamic moral economy. Therefore, this qualitative paper aims to offer basic comparisons between the conventional moral economy and Islamic moral economy. Later, we bring into discussion another neologism; universal man, as proposed by Mahyudi and Abdul Aziz (2017). This inclusion is relevant in light of effective policy formulation. Thus, this paper also seeks to determine the role of the universal man concept in the common discourse of conventional and Islamic moral economy. From thereon, the probable influence of the universal man concept in furthering the moral economy agenda is explored. The expected implication of this paper lies in the aspect of policy design in such a way that it could help to propose private and public strategies to develop a functioning moral economy.